Interpersonal communication - Floyd, Kory (New York : McGraw-Hill, 2011)
Demonstrates how effective interpersonal communication can make students' lives better. With consideration given to the impact of computer-mediated communication, this title helps students understand and build interpersonal skills and choices for their academic, personal, and professional lives
1. About communication -- 2. Culture and gender -- 3. Communication and the self -- 4. Interpersonal perception -- 5. Language -- 6. Nonverbal communication -- 7. Listening -- 8. Emotion -- 9. Interpersonal communication in friendships and professional relationships -- 10. Interpersonal communication in romantic and family relationships -- 11. Interpersonal conflict -- 12. Deceptive communication
Includes bibliographical references and index
Keywords: Interpersonal communication